2021
DOI: 10.1172/jci.insight.148182
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CT and telomerase-positive circulating tumor cells improves diagnosis of small pulmonary nodules

Abstract: BACKGROUND Early diagnosis and treatment are key to the long-term survival of lung cancer patients. Although CT has significantly contributed to the early diagnosis of lung cancer, there are still consequences of excessive or delayed treatment. By improving the sensitivity and specificity of circulating tumor cell (CTC) detection, a solution was proposed for differentiating benign from malignant pulmonary nodules. METHODS In this study, we used telomerase reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The oHSV1-hTERTp-GFP was designed by replacing the endogenous ICP4 promoter with a TERT promoter and replacing the genes encoding cell protein 34.5 (ICP34.5) with a GFP gene as described before (7,8). The purified viruses were stored at −80 ℃ until use.…”
Section: Ctcs Detection Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oHSV1-hTERTp-GFP was designed by replacing the endogenous ICP4 promoter with a TERT promoter and replacing the genes encoding cell protein 34.5 (ICP34.5) with a GFP gene as described before (7,8). The purified viruses were stored at −80 ℃ until use.…”
Section: Ctcs Detection Reagentsmentioning
confidence: 99%
“…Collected 4 milliliters of prebiopsy PB with ethylene diamine tetraacetic acid (EDTA) tubes and kept them at 4 ℃ until separation. Sample preparation and detailed workflow were carried out as previously described (7,8). In brief, the oHSV1-hTERTp-GFP was used to infect the cells after lysis of red blood cells, then infected cells were incubated at 5% CO 2 and 37 ℃ cell incubator for 24 h. The transduced cells were collected, then stained with an anti-CD45 antibody (Biolegend, San Diego, CA, USA; Cat: 304014) and anti-PSMA antibody (Biolegend, Cat: 342508).…”
Section: Peripheral Blood (Pb) Sampling and Ctc Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, 4 although the authors found that the multiparametric approach did not improve the diagnostic performance of the K parameter, the study was headed in the right direction. Moreover, it is worth mentioning that combined imaging techniques and serological markers, such as circulating tumor cells or tumor markers, have been a popular approach in tumor diagnosis due to their unique advantages 7,8 . Therefore, except for the combination of imaging parameters, magnetic resonance imaging (MRI) methods combined with serological markers are expected to become a novel strategy for differentiating benign and malignant musculoskeletal tumors.…”
mentioning
confidence: 99%
“…Moreover, it is worth mentioning that combined imaging techniques and serological markers, such as circulating tumor cells or tumor markers, have been a popular approach in tumor diagnosis due to their unique advantages. 7,8 Therefore, except for the combination of imaging parameters, magnetic resonance imaging (MRI) methods combined with serological markers are expected to become a novel strategy for differentiating benign and malignant musculoskeletal tumors. In addition, as artificial intelligence techniques continue to develop, radiomics has shown a great potential in cancer diagnosis, prognosis, and treatment.…”
mentioning
confidence: 99%